Acute HIT session induced changes and recovery in muscle activation level, voluntary force production and jump performance during 8 weeks of HIT training in recreationally endurance trained men - Polomoshnov, Dmitrii (2017)
High-intensity interval training (HIT) has gained wide popularity among competitive athletes and sport enthusiasts in the recent decades. While an extensive amount of research has been done on acute neuromuscular (NM) response and recovery after low-moderate intensity endurance training, the data regarding HIT in recreational athletes remains to be limited. In order to reduce that gap, the present study investigated the acute HIT session induced changes and recovery in muscle activation level, voluntary force production and counter movement jump performance during 8 weeks of HIT training in recreationally endurance trained men. A total of 9 subjects age 30.7 years (± 5.8), participated in the present study. The subject completed 8 weeks HIT training period (3-5 HIT sessions per week). NM measurements took place at weeks -1, 4 and post 8, respectively. The measurements included isometric unilateral knee extension with electrical stimulation and a counter movement jump (CMJ). NM measurements were performed before, after and 24 h after the HIT session at weeks -1, 4 and post 8, respectively. There was an acute decrease in maximal voluntary contraction (MVC) and muscle activation level (AL) following HIT sessions, while a significant decrease was observed only at week 4, being 12.3 % ± 8.6 for MVC and 8.2 % (± 7.9) for AL respectively. CMJ performance was significantly enhanced after the HIT session at weeks -1 (8.0 % ± 6.3) and 4 (7.7 % ± 6.8). MVC capacity was recovered within 24 hours post HIT and no potentiation of CMJ was any more present. The major findings of the study showed that isometric MVC and muscle AL of lower extremities can be significantly impaired after HIT, while jumping ability can be enhanced due to post activation potentiation (PAP). The magnitude of the changes is highly individual. However, in recovery of 24 hours post session PAP was not observed any more as well as MVC and AL impairment.